2014
DOI: 10.3892/ijmm.2014.1625
|View full text |Cite
|
Sign up to set email alerts
|

Role of miR-200c/miR-141 in the regulation of epithelial-mesenchymal transition and migration in head and neck squamous cell carcinoma

Abstract: Epithelial-mesenchymal-transition (EMT) is a critical step in tumor invasion and metastasis, while its fate is mainly defined by the balanced expression between the miR-200 family and ZEB transcription factors. In this study, we observed a reciprocal correlation between miR-200c/mir-141 and ZEB1, as well as between ZEB2 and E-cadherin expression in a panel of 13 head and neck squamous cell carcinoma (HNSCC) cell lines. We also confirmed that the enforced expression of miR-200c and miR-141 significantly reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
58
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 22 publications
9
58
0
1
Order By: Relevance
“…As Aza treatment markedly upregulated the expression levels of miR-200c, the results of the present study suggest that miR-200c may have a suppressive effect on ccRCC cell migration and invasion, and the inhibitory effect of Aza treatment on ccRCC cell migration and invasion may be partly due to the direct upregulation of miR-200c expression levels. A suppressive role of miR-200c in cell migration and invasion has additionally been identified in other types of human cancer (23,24). Liu et al (13) identified that miR-200c inhibited invasion, migration and proliferation of bladder cancer cells.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As Aza treatment markedly upregulated the expression levels of miR-200c, the results of the present study suggest that miR-200c may have a suppressive effect on ccRCC cell migration and invasion, and the inhibitory effect of Aza treatment on ccRCC cell migration and invasion may be partly due to the direct upregulation of miR-200c expression levels. A suppressive role of miR-200c in cell migration and invasion has additionally been identified in other types of human cancer (23,24). Liu et al (13) identified that miR-200c inhibited invasion, migration and proliferation of bladder cancer cells.…”
Section: Discussionmentioning
confidence: 96%
“…MicroRNAs (miRs) are a type of small non-coding RNA (19)(20)(21)(22)(23)(24)(25) nucleotides) that possess prominent roles in the regulation of genes (6). MiRs typically inhibit gene expression by directly binding the 3'-untranslated region of their target messenger (m)RNAs, causing repression of translation or mRNA degradation (7).…”
Section: Introductionmentioning
confidence: 99%
“…The present study indicated that miR-200c is associated with lymph node metastasis, suggesting that miR-200c may be upregulated in the metastatic process. However, miRNA-200c has been shown to restrict the epithelial-mesenchymal transition (EMT) and metastasis through direct targeting of the cell adhesion pathway (27,28), particularly the zinc finger E-box binding homeobox (ZEB)-cadherin 1 axis (29). However, the pleiotropic effect of miR-200c in the metastatic process is contradictory in in vitro and in vivo studies (30).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor invasion and metastasis have previously been demonstrated to be tightly controlled by the balanced expression of the miR-200 family members and zinc finger E-box-binding homeobox (ZEB) transcription factors (9,11). In previous studies, it has been demonstrated that miR-200 expression is downregulated within cancer cells, enabling a positive regulatory loop to maintain ZEB1/ZEB2 expression (11,13). Inhibition of miR-200 reduces E-cadherin expression, increases vimentin expression and induces the EMT mechanism (14).…”
Section: Dysregulation Of Mir-200 Family Micrornas and Epithelial-mesmentioning
confidence: 99%